2021
DOI: 10.3390/en14123493
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Battery Model with Aging Dependency

Abstract: Designed to store and discharge electrical energy, rechargeable batteries consist of elementary storage cell assemblies. Aging is affected by various aggravating factors, mainly temperature. There are many electric or electrochemical models which describe their operation. Most standard models do not consider the aging phenomena of batteries and their consequences, while batteries deteriorate when used or stored. Precisely, most battery models do not simulate the influence of cell aging on other cells. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Additionally, storage degradation and battery inefficiencies during a certain period of operation are susceptible to battery operating limits and energy trading needs, as stated by Li et al [4]. It is advised that the battery's operating cycle should be kept in its safe thermal limit to extend its life [35]. This is due to the battery's usable capacity and prospective electricity prices being both influenced by the grid's state and execution time [24].…”
Section: Fuzzy Logic Designmentioning
confidence: 99%
“…Additionally, storage degradation and battery inefficiencies during a certain period of operation are susceptible to battery operating limits and energy trading needs, as stated by Li et al [4]. It is advised that the battery's operating cycle should be kept in its safe thermal limit to extend its life [35]. This is due to the battery's usable capacity and prospective electricity prices being both influenced by the grid's state and execution time [24].…”
Section: Fuzzy Logic Designmentioning
confidence: 99%
“…According to the statistical data of oil and gas and mining companies (Koteleva et al, 2021), the reasons for the failures of induction motors are the defects shown in Figure 1. Existing approaches to improving efficiency, ensuring optimal dynamic and energy characteristics (Vasilyeva et al, 2021;Savard et al, 2021) as well as maintaining performance are largely based on the scalar control system of the electric drive. Analysis of research has shown the relevance of developing control algorithms for electric drive systems, taking into account the presence of defects in the IM (Sychev et al, 2022;Klyuev et al, 2021).…”
Section: Induction Motors Deterioration and Defectsmentioning
confidence: 99%
“…The voltage dispersion between cells measures the variation of discharge between the different battery cells [15]. It is interesting, especially in batteries without BMS, as it can indicate battery malfunction that is not able to balance the discharge between the cells [16]. This indicator can also be used to compare the state of the different cells within the battery.…”
Section: Voltage Dispersion Between Cellsmentioning
confidence: 99%